Kimura’s disease: a rare post auricular recurrence - Patel, Tithi B.; Sharma, Rachit Y.; Shah, Drashya V.; Shah, Vipulkumar V. (International Journal of Research in Medical Sciences, 2024)
Kimura’s disease is a rare, chronic inflammatory condition of unknown cause, predominantly affecting individuals of Southeast Asian descent. It typically manifests in the head and neck region, presenting as deep subcutaneous nodules or masses, with peripheral blood eosinophilia and elevated serum immunoglobulin E (IgE) levels. Regional lymphadenopathy and salivary gland involvement are often associated with the disease. We report a case of a 38-year-old Indian woman diagnosed with Kimura’s disease. She presented with a painless swelling on the right side of her face, located behind the ear, which had been gradually increasing in size over six months. Routine hematological, imaging, and histopathological evaluations confirmed the diagnosis. The patient was started on prednisolone at a dosage of 1 mg/kg/day, with close monitoring and additional supportive treatment. She showed remarkable clinical improvement, with a substantial reduction in the size of the swelling and lymph nodes, exceeding 50%. This case underscores the importance of considering Kimura’s disease in the differential diagnosis for middle-aged South Asian adults with gradually expanding facial swellings. It also emphasizes the significance of early diagnosis and prompt intervention to reduce complications and facilitate quick recovery.